A new method on Box dimension of Weyl-Marchaud fractional derivative of Weierstrass function. (January 2021) - Yao, Kui; Chen, Haotian; Peng, W.L.; Wang, Zekun; Yao, Jia; Wu, Yipeng
Abstract: A new method is applied to calculating fractal dimensions of fractional calculus of some fractal functions, by this method, we obtain Box dimension of Weyl-Marchaud fractional derivative of Weierstrass function.